LITERASI PERPAJAKAN PPH ORANG PRIBADI DALAM PENGELOLAAN KEUANGAN INDIVIDU PADA MAHASISWA POLITEKNIK PAJAJARAN ICB BANDUNG - Gunardi Gunardi; Vina Anggilia Puspita; Ramayani Yusuf (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
This study aims to analyze the effect of tax literacy on individual financial management with tax risk and investment risk as moderating variables among Accounting Study Program students at Politeknik Pajajaran ICB Bandung. The study employed a quantitative approach using descriptive and verificative methods. The sampling technique used was total sampling with a total of 100 student respondents. Data were collected through questionnaires using a Likert scale and analyzed using linear regression analysis and Moderated Regression Analysis (MRA). The results showed that tax literacy has a positive and significant effect on individual financial management. The higher the students’ level of tax understanding, the better their ability to manage personal finances. Tax risk and investment risk were also proven to strengthen the relationship between tax literacy and individual financial management. The findings indicate that tax understanding not only improves tax compliance but also helps individuals in financial planning and making more rational economic decisions. This study implies that tax education needs to be integrated with financial literacy education in order to improve the quality of financial management among the younger generation.